DIFFERENCES BETWEEN THE CONCEPTS OF PHYSICAL QUALITY AND PHYSICAL ABILITY - Luqmonov , Subhonjon Shavqiddin o‘g‘li (Educational Research in Universal Sciences, 2024)
This article examines the differences between the concepts of physical quality and physical ability, their understanding, as well as their common and different aspects.